Festive movie features - Salman, Ali Sabah; Ajil, Abbas Ali (Al-Adab Journal, 2020)
The topic of the features of the festive movie was not raised previously, nor was it established and prepared for it, therefore there is a precedent and difficulty in establishing and elaborating the features of this type of film, especially in the works of Prince of Costa Rica that have common features that we can call festive, which are different from the storytelling or watching. Or carnival, although all of these designations extend their roots to the ceremonial rituals of the peoples, which were embodied in the (Akito) ceremonies of the Babylonians, and the Greeks in the celebrations of Bakhos, as well as associated with rituals and festivals, which later turned to include festivals and worldly ceremonies. From its inception in the Greek incubator, the theater presented patterns of ceremonialness in the theater, specifically its first beginnings with the choir, and then the emergence of the single actor alternating with the choir. There is also the name of the ceremonial theater. But in the cinema, which is the most recent history of the theater that is deeply rooted in history, many directors have presented films bearing the characteristics of celebration, storytelling, spectacle and carnival.